The false negative rate and the role for virtual review in a nationally evaluated glaucoma referral refinement scheme. (18th June 2015) - Ratnarajan, Gokulan; Kean, Jane; French, Karen; Parker, Mike; Bourne, Rupert
Abstract Purpose To establish the safety of the CHANGES glaucoma referral refinement scheme (GRRS). Methods The CHANGES scheme risk stratifies glaucoma referrals, with low risk referrals seen by a community based specialist optometrist (OSI) while high risk referrals are referred directly to the hospital. In this study, those patients discharged by the OSI were reviewed by the consultant ophthalmologist to establish a 'false negative' rate (Study 1). Virtual review of optic disc photographs was carried out both by a hospital‐based specialist optometrist as well as the consultant ophthalmologist (Study 2). Results None of these 34 discharged patients seen by the consultant were found to have glaucoma or started on treatment to lower the intra‐ocular pressure. Five of the 34 (15%) were classified as 'glaucoma suspect' based on the appearance of the optic disc and offered a follow‐up appointment. Virtual review by both the consultant and optometrist had a sensitivity of 80%, whilst the false positive rate for the optometrist was 3.4%, and 32% for the consultant (p < 0.05). Conclusions The false negative rate of the OSIs in the CHANGES scheme was 15%, however there were no patients where glaucoma was missed. Virtual review in experienced hands can be as effective as clinical review by a consultant, and is a valid method to ensure glaucoma is not missed in GRRS. The CHANGES scheme, which includes virtual review, is effective at reducing referrals to the hospital whilst not compromising patient safety.